Potholes in the road : transition problems for low-income youth in high school - Sánchez-Jankowski, Martín, 1945- (University of California Press, 2022)
"As education has been increasingly lauded as the path to achieving the 'American Dream,' Martín Sánchez-Jankowski utilizes extensive participant observation to examine how low-income students navigate the education system. With compassion and rigor, Potholes in the Road explores the dynamics of the multiple interrelated obstacles that low-income students must surpass in order to make educational transitions successfully from high school to college. Using extensive ethnographic research, Sánchez-Jankowski explores the mythic pull of the 'American Dream' and how obstacles of social capital, wealth, and culture make achieving such a dream through education nearly impossible"--